Radiographic analysis of factors predisposing toward tendon tears in the knee extensor mechanism - Rodrigo Pires e Albuquerque; André Luiz Siqueira Campos; José Félix dos Santos Neto; Evaldo Karam; José Guilherme Neves; Paulo Di Tullio; Vincenzo Giordano; Ney Pecegueiro do Amaral (Revista Brasileira de Ortopedia, 2014)
Objectives:To review radiographs of patients who suffered tendon tears of the knee extensor apparatus and observe alterations that might be factors predisposing toward this type of injury.Methods:We retrospectively analyzed 60 cases of injury to the knee extensor mechanism that were treated surgically at the Miguel Couto Municipal Hospital between March 2004 and March 2011. Four patients were excluded due to poor quality of the examination.Results:Of the 56 patients evaluated, 23 were considered to be normal and 33 presented radiographic alterations. Among these, eight (24.3%) presented suprapatellar osteophytes alone; seven (21.2%), infrapatellar calcification; seven (21.2%), suprapatellar calcification; six (18.2%), supra- and infrapatellar osteophytes; and five (15.1%), infrapatellar osteophytes alone.Conclusion:Radiographic alterations were frequently observed in patients with extensor mechanism tears.